Health-Related Quality of Life among Elderly Population of Bangladesh (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Elderly population in Bangladesh is one of the largest in the world in term of absolute number and ageing is an emerging problem. Elderly are at risk from non-communicable diseases as well as mental problems and health-related quality of life (HRQoL) affects in urban and rural elderly.Objective: To find out and compare HRQoL in urban and rural elderly population of Bangladesh.Materials and Methods:A comparative cross-sectional study was carried out to compare HRQoL in urban and rural elderly. This was a two samples study; 130 each from urban and rural. Total 260 elderly were selected conveniently. Data were collected through face to face interview using a pre-tested semi structured questionnaire of SF-36 v2 HRQoL survey.  This study was carried in urban elderly residing in Ward number 3, Race Course, Cumilla City Corporation and in rural elderly residing in Noapuskuni Village of Babutipara Union, Muradnager Upazila, Cumilla. This one-year study was conducted from 15 July 2017 to 14 June 2018.Results: Majority of the elderly were Muslim (91.5%), female (53.5%), married (59.6%) and from joint family (91%). The mean ± SD age of elderly was 69.26±6.337 years and mean ± SD monthly family income was Tk. 16561.54±9192.076. SF- 36 v2 HRQoL scale; a licensed software-based survey tool was used measure the health-related quality of life of elderly.  Most of the elderly were found with average physical component summary (PCS) (53.1%) and mental component summary (MCS) (50.8%) of HRQoL. Age had significant negative correlation with PCS (p